Use of Agricultural Vocabulary in English Lessons - Khushbakovna, Shoynazarova Vazira; qizi, Ergasheva Umida Asad (European Journal of Life Safety and Stability (2660-9630), 2023)
This article discusses the need to expand agricultural vocabulary for English language teaching materials for students in agricultural programs. Basically, it is aimed at a specific goal - the use of agricultural vocabulary in English classes. Recognizing the need for targeted teaching of vocabulary learning strategies to improve the status quo and contribute to the professional profile, agricultural English teachers are using academic language based on the diversity of agricultural terminology. they should develop the horse.